Implementasi Model Pembelajaran Problem Based Learning (PBL) Berbantu LKPD Akuntansi Berbasis Bukti Transaksi Untuk Meningkatkan Hasil Belajar Akuntansi Dasar Siswa - Alfiana, Nur; Oknaryana, Oknaryana (Universitas Negeri Padang, 2025)
This research aims to improve students learning outcomes in accounting subjects through the implementation of the Problem based leaarning (PBL) model assisted by Student Worksheets (LKPD) based on transaction evidence. The research used Classroom Action Research (CAR) conducted in two cycles involving 35 students of class X Accounting 4 at SMK Negeri 2 Padang. Data were collected through observation, tests, and documentation. Evaluation instruments included a pretest, daily tests in cycle I and II, and a posttest to measure students' learning outcomes. The results showed a significant increase in the percentage of students who met the minimum passing criteria, from 5.71% in the pretest to 42.86% in the first cycle, and further increased to 82.86% in the second cycle and posttest. Additionally, the teacher’s activity in implementing the learning process improved significantly, categorized as very good. Thus, the application of the PBL model assisted by transaction-based LKPD is proven effective in enhancing students’ accounting learning outcomes and fostering an active, contextual, and meaningful learning environment.